Meaning and Usage Of Adjectives Ending In - Able/-Ible - Aris Munandar (Humaniora, 2002)
The study on –able and adjectives ending in –able/-ible (Munandar, 1999:74-82) was done based on historical analysis. The study revealed the role of etymology of words in the divergence of the suffix –ible and -able. It discusses that in the course of its development, English got influences from Latin, French, Scandinavian, and other languages. The most outstanding influences, however, are those of Latin and French. From Latin and French , English had adopted many words and other elements to fulfil the need for adequate expressions. These borrowings are preserved to their strong influence (high productivity) up to the present use. The origin of words is ,thus, worth knowing not only of its possible explanation for the rule of deriving adjectives with the suffix –able/-ible, but also of its relationship to determine the meaning of adjectives formed from words which are not of current use. This is in line with Marckwardt (1960:177) who assumed that the etymology of a word may serve as a guide to its proper use and meaning, although current usage is the only scientifically valid criterion to define the meaning. The presentation of meaning and usage in this article will demonstrate how that assumption works. Some adjectives are assigned with meanings in present usage different from those of the etymology of basewords. While some others whose basewords are not found in current use are recognized after the origin of the basewords are revealed. The tracking of origin is done by looking up two dictionaries: The Oxford Dictionary of English Etymology and The Old English Dictionary. The findings are cross-checked with the current meaning and usage in the Oxford Advanced Learner’s Dictionary of Current English.